Perspectives, fears and expectations of patients with gynaecological cancers during the COVID‐19 pandemic: A Pan‐European study of the European Network of Gynaecological Cancer Advocacy Groups (ENGAGe) - Murat Gültekin; Sertaç Ak; Ali Ayhan; Aleksandra Strojna; Andrei Pletnev; Anna Fagotti; Anna Myriam Perrone; Bilal Emre Erzeneoglu; Bilal Esat Temiz; Birthe Lemley; Burcu Soyak; Cathy Hughes; et al. (2020)
Background: The impact of the COVID-19 pandemic on European gynaecological cancer patients under active treatment or follow-up has not been documented. We sought to capture the patient perceptions of the COVID-19 implications and the worldwide imposed treatment modifications. Methods: A patient survey was conducted in 16 European countries, using a new COVID-19-related questionnaire, developed by ENGAGe and the Hospital Anxiety & Depression Scale questionnaire (HADS). The survey was promoted by national patient advocacy groups and charitable organisations. Findings: We collected 1388 forms; 592 online and 796 hard-copy (May, 2020). We excluded 137 due to missing data. Median patients’ age was 55 years (range: 18–89), 54.7% had ovarian cancer and 15.5% were preoperative. Even though 73.2% of patients named cancer as a risk factor for COVID-19, only 17.5% were more afraid of COVID-19 than their cancer condition, with advanced age (>70 years) as the only significant risk factor for that. Overall, 71% were concerned about cancer progression if their treatment/follow-up was cancelled/postponed. Most patients (64%) had their care continued as planned, but 72.3% (n = 892) said that they received no information around overall COVID-19 infection rates of patients and staff, testing or measures taken in their treating hospital. Mean HADS Anxiety and Depression Scores were 8.8 (range: 5.3–12) and 8.1 (range: 3.8–13.4), respectively. Multivariate analysis identified high HADS-depression scores, having experienced modifications of care due to the pandemic and concern about not being able to visit their doctor as independent predictors of patients’ anxiety. Interpretation: Gynaecological cancer patients expressed significant anxiety about progression of their disease due to modifications of care related to the COVID-19 pandemic and wished to pursue their treatment as planned despite the associated risks. Healthcare professionals should take this into consideration when making decisions that impact patients care in times of crisis and to develop initiatives to improve patients’ communication and education.